Facile Synthesis, Characterization and Biocatalytic Application of Imidazolium-Based Chiral Ionic Liquids - Ng, Shie Ling (2008)
In view of the emerging importance of ionic liquids as reaction media in organic synthesis, researchers have recently focused on the synthesis of chiral ionic liquids (CILs) for their particularly potential applications to chiral discrimination. The study of the application of CILs in asymmetric synthesis is not only an opportunity but also a challenge for researchers. Herein, the synthesis of new CILs based on alkyl-imidazole as the cation and four different chiral acids as the anion were reported. Eighteen chiral ionic liquids were synthesized and characterized by a variety of physico-chemical techniques. Four different chiral acids chosen were L-lactic acid, L-tartaric acid, (R)-(-)-camphor-10-sulfonic acid and L-malic acid. Imidazole was chosen because they are easier to prepare and less toxic compared to thiazole and pyrrolidine which contain sulfur and nitrogen compounds respectively. These salts were prepared using simple ion-exchange reaction which gave good overall yield (> 95 %) at room temperature. All the CILs synthesized are hygroscopic. Their enantiomeric purity was analyzed using 1H NMR spectroscopy. The effect of alkyl substituents bonded to the nitrogen on imidazolium cation on the physical properties especially its melting point was also examined and observed. The melting points for bulkier ionic liquids are higher as compared to those of small ionic liquids. For the solid CILs, their solubility in organic solvents were tested and followed by recrystallization. Their three dimensional network of cation-anion and hydrogen bonding were analyzed by single-crystal X-ray diffraction analysis. Each CILs optical polarity was measured using polarimeter. An example of the application of CILs is in biocatalysis. Chiral ionic liquid coated-enzyme (CILCE) was prepared by coating Candida rugosa lipase with 1-hydrogen-3-hexylimidazolium hydrogen-tartrate. CILCE was then used to catalyze some non-chiral and chiral esterification reactions. For non-chiral esterification, we found that CILCE gave higher percentage of conversion compared to native enzyme for short and medium chain acids, where all acids were reacted with oleyl alcohol. For chiral esterification, enantioselective esterification of (±)-menthol with butyric anhydride was studied. Percentage conversion of menthyl butyrate in CILCE (81.91 %) was better than in CRL (28.19 %). However, its enantiomeric excess (ee) from CILCE was low compared to CRL with 1.1 and 3.3, respectively calculated from its enantiomeric value, E.